Pengembangan Aplikasi Pelindung Perempuan Pada Pendidikan Vokasi - Rafsanjani, Rafsanjani; Sutisna, Nuurshofiah (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2021)
The acts of violence and harassment experienced by women on social media can be found easily in social media comments. Comments given by other people can have a very bad effect on the owner of the social media. The forms of violence and harassment against women on social media may not directly affect the victim physically, but will have an impact on the psychological victim. The psychological impact of the experience of violence on women is generally indicated by the act of looking at yourself negatively, blaming yourself a lot, and feeling negative feelings that arise. And the worst effect is to end one's life. Hi this is of course very unfortunate if it happens and continues to increase. Women who are victims of violence and harassment on social media not only suffer psychologically, but will also experience prolonged trauma that does not rule out the possibility of ending up with suicide attempts..